IMPACT OF GOVERNANCE AND ECONOMIC FACTORS ON INFORMAL EMPLOYMENT IN WEST AFRICA - Oluwaseun Isiaka Adekoya; Musa Ilias Biala (Malete Journal of Accounting and Finance)
Understanding the drivers of informal employment would go a long way in addressing such problems as underdevelopment, poverty, and unemployment. Therefore, this study investigates the impact of governance and economic factors on informal employment in West Africa. The governance factors considered are control of corruption, government effectiveness, quality of governance, regulatory quality, rule of law, political stability and absence of violence as well as voice and accountability, while the economic factors are income per capita, unemployment rate, tax burden, inflation rate, and household spending. The neo-liberal model is the theoretical framework underlying the study. Using panel dataset collected on 16 West African countries for the period of 2010-2020, the study estimated the fixed and random effects regressions of the model. The results show that quality of governance, unemployment rate, per capita income and urban population all had a negative impact on informal employment. Therefore, quality of governance, unemployment rate, per capita income and urban population negatively influence the proliferation of informal employment. Hence, policymakers should focus on improving the quality of governance, reducing the unemployment rate, increasing the income per capita, and controlling the urban population in order to discourage informality in West Africa.